SHORT STORY WRITING BOOK DEVELOPMENT WHICH ORIENTED IN FORM OF CREATIVITY - Agung Nasrulloh Saputro; Panji Kuncoro Hadi; Suryo Ediyono (Universitas Sebelas Maret, 2017)
This research is a development research that tries to develop self-based potential poetry writing book. This development research refers to the Borg and Gall stage model. The stage consists of ten stages of development, there are the initial research and information collection stage, the planning stage, the initial stage of production format development, the initial test phase, the product revision phase, the field test phase, the product revision phase, the field test phase, the product revision phase end, and dissemination and implementation. In this study, only until the final product revision stage without including the phase of dissemination and implementation due to limited time research. In general, this study aims to explain the process of developing and implementing textbook writing short stories oriented on the formation of characters. While the subject in this study is the students of class VIII SMP N 1 Mantingan Ngawi.Penelitian this time is a development research for trying to develop textbooks. The results of the textbook development process are shown in the following stages. The validation of textbooks was assessed by two validators, validation results indicated that the textbooks were included in either category because of the percentage of ≥ 75%, the initial trial results were trialed in limited to seven students of class X generated by student questionnaires, teacher interviews, and observer observations. From the results of field trials resulted in the value of students in writing short stories to produce the average value of students 80. Implementation of textbooks write a short story-oriented writing the formation of the character of student activities at the time of writing short story writing using textbook writing a short story-oriented character formation. Activities at the time of learning are divided into three, namely observation, interviews with teachers, and student questionnaires. Based on these data it can be analyzed that the learning of writing a short story-oriented writing on the character of this worthy as a textbook.